2000
DOI: 10.1263/jbb.90.234
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology of Nitrifying Bacteria in Wastewater Treatment Process Examined by Fluorescence In Situ Hybridization.

Abstract: The microbial ecology of nitrifying bacteria in various types of wastewater treatment processes and the dynamic response of the microbial ecology in biofilms were investigated using fluorescence in situ hybridization (FISH) with 16S rRNA-targeted oligonucleotide probes. Nitrifying bacteria were found to exhibit various organizational forms under different conditions of substrate composition and concentration. Ammonia-oxidizing bacteria were dominant in ammonia-rich inorganic wastewater, while heterotrophic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The species and characteristics of AOB were found to be strongly affected by the reactor operational conditions such as substrate composition and concentration in a WWTP. The results indicated that effective control of the microbial ecology by controlling the conditions of the reactor operation could be applied to engineered systems with direct monitoring using FISH (Aoi et al 2000). During experiments carried out with freshwater aquaria, FISH analysis revealed that Nitrosomonas marina-like AOB may outcompete Nitrosomonas tenius-like AOB in the low-ammonia concentration environment of an aquarium, whereas Nitrosomonas europea-like AOB were found only in reactors with a history of high ammonia concentrations (Burrell et al 2001).…”
Section: Fluorescence In Situ Hybridization Techniquementioning
confidence: 99%
“…The species and characteristics of AOB were found to be strongly affected by the reactor operational conditions such as substrate composition and concentration in a WWTP. The results indicated that effective control of the microbial ecology by controlling the conditions of the reactor operation could be applied to engineered systems with direct monitoring using FISH (Aoi et al 2000). During experiments carried out with freshwater aquaria, FISH analysis revealed that Nitrosomonas marina-like AOB may outcompete Nitrosomonas tenius-like AOB in the low-ammonia concentration environment of an aquarium, whereas Nitrosomonas europea-like AOB were found only in reactors with a history of high ammonia concentrations (Burrell et al 2001).…”
Section: Fluorescence In Situ Hybridization Techniquementioning
confidence: 99%
“…Nitrosomonas traditionally have been considered the most important bacteria for NH 3 oxidation [23]. Furthermore, Nitrosospira and Nitrosomonas have both been recently found in activated sludge [1], freshwater lakes [30] and estuaries [5]. There is culturebased evidence that Nitrosospira strains may be more common in soils [2].…”
Section: Introductionmentioning
confidence: 99%
“…The probe concentration was 0.5 ng/l. Hybridization was followed by a stringent washing step at 48°C for 20 min in a washing buffer containing Tris-HCl (20 mM, pH 7.4), NaCl (35 mM) (5,16), and sodium dodecyl sulfate. The washing buffer was removed by rinsing the slides with ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in situ hybridization with fluorescencelabeled oligonucleotide probes has been widely used for in situ analysis of microbial communities, such as a biofilm in a wastewater treatment process (5,18,22,29). This method relies on the presence of many target sequences within an individual cell.…”
mentioning
confidence: 99%